Is tumor testing efficiency for Lynch syndrome different in rectal and colon cancer?. Issue 12 (December 2020) - Marabelli, Monica; Gandini, Sara; Rafaniello, Paola Raviele; Calvello, Mariarosaria; Tolva, Gianluca; Feroce, Irene; Lazzeroni, Matteo; Marino, Elena; Dal Molin, Matteo; Trovato, Cristina; Guerrieri-Gonzaga, Aliana; Petz, Wanda Luisa; et al.
Abstract: Background: Tumor testing utility in Lynch syndrome (LS) diagnosis is established. Aims: Analyze the differences between tumor testing efficiency in rectal (RC) and colon cancer (CC). Methods: We performed immunohistochemistry (IHC) for MisMatch Repair (MMR) proteins (IHC-MMR) and MicroSatellite Instability analysis (MSI) on 482 unselected primary tumors: 320 CCs and 162 RCs. Samples had proficient-IHC, deficient-IHC or borderline-IHC ("patchy" expression). MSI-H borderline-IHC tumors were considered as likely MMR-deficient. Germline testing was offered to MMR-deficient patients without BRAF mutation or MLH1 promoter hypermetilation ( MLH1 -Hy). Results: We identified 51/482 (10.6%) MMR-defective tumors. Multivariable analysis demonstrated a significant correlation between tumor testing results with histotype, lymph-node involvement and tumor location. In particular, RC showed a lower MMR-deficiency rate than CC ( p <0.0001). Interestingly, MLH1 loss was detected in 0% RCs and 76.1% CCs, with 80% of them showing BRAF mutation/ MLH1 -Hy. A germline variant was detected in 12 out of 18 patients (mutation detection rate of 66.7%). Conclusion: Tumor testing results showed molecular differences between CCs and RCs, in terms of MMR proteins expression, and presence of BRAF mutation/ MLH1 -Hy. MSH6 variants were the most frequent ones (50%). Although young age at diagnosis was associated with mutation detection ( p = 0.045), 33.3% of LS patients were >50 years.